IBM SMP NEGERI 4 DENPASAR - Arjaya, Ida Bagus Ari; Javandira, Cokorda (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
SMP 4 Denpasar holds the title of "Adiwiyata School" in academic year 2012/2013. However, in 2016 SMP Negeri 4 Denpasar can not achieve Adiwiyata school title, whereas potentially a comfortable and beautiful school environment as well as awareness of the party as to the environment is very good preservation. Based on the interview with the Principal of SMP Negeri 4 Denpasar, Drs. I Wayan Dhania, M.Pd. He expressed the need to re-arrange the school environment by giving the scientific name of each plant so that SMP Negeri 4 Denpasar can regain the title of Adiwiyata School. Besides it is related to the learning process, although there are already teachers who are able to develop e-learning based online learning in SMP Negeri 4 Denpasar. But the number is still very minimal and only limited use of blogs with simple features. The method used in this research is the interview method that is the way interviewer deeply with resource, discussion method, active participation method, and the method of demonstration. Based on the implementation of the program it can be concluded 1) The creation of e-learning module that is schoology and plantamor is very useful for teachers in SMP 4 Denpasar because it has features that facilitate the teacher in the teaching, 2) e-learning training is schoology and plantamor implemented in SMP Negeri 4 Denpasar teleah went smoothly, although the teachers are a little constrained by making schoology account that requires special precision, 3) Provision of scientific naming board of IbM program is very useful in supporting science teaching especially biology, 4) There is a difference between the results of pre test and post test teachers of SMP Negeri 4 Denpasar (p-value = 0.013> ? = 0.05).